Inherited DNA lesions determine G1 duration in the next cell cycle. Issue 1 (2nd January 2018) - Lezaja, Aleksandra; Altmeyer, Matthias
ABSTRACT: Replication stress is a major source of DNA damage and an important driver of cancer development. Replication intermediates that occur upon mild forms of replication stress frequently escape cell cycle checkpoints and can be transmitted through mitosis into the next cell cycle. The consequences of such inherited DNA lesions for cell fate and survival are poorly understood. By using time-lapse microscopy and quantitative image-based cytometry to simultaneously monitor inherited DNA lesions marked by the genome caretaker protein 53BP1 and cell cycle progression, we show that inheritance of 53BP1-marked lesions from the previous S-phase is associated with a prolonged G1 duration in the next cell cycle. These results suggest that cell-to-cell variation in S-phase commitment is determined, at least partially, by the amount of replication-born inherited DNA damage in individual cells. We further show that loss of the tumor suppressor protein p53 overrides replication stress-induced G1 prolongation and allows S-phase entry with excessive amounts of inherited DNA lesions. Thus, replication stress and p53 loss may synergize during cancer development by promoting cell cycle re-entry with unrepaired mutagenic DNA lesions originating from the previous cell cycle.